Toxicity of engineered metal oxide nanomaterials mediated by nano–bio–eco–interactions: a review and perspective. Issue 6 (25th September 2015) - He, Xiaojia; Aker, Winfred G.; Fu, Peter P.; Hwang, Huey-Min
Abstract : This is a comprehensive review on the toxicity of metal oxide nanomaterials regarding their environmental interactions at the nano–bio–eco interface. Abstract : Along with the expanding use of engineered metal oxide nanomaterials (MONMs), there is a growing concern over their unintentional adverse toxicological effects on human health and the environment upon release and exposure. It is inevitable that biota will be exposed to nanomaterials, through intentional administration or inadvertent contact under such circumstances. Therefore, a thorough investigation of the potential nanotoxicity of MONMs at the nano–bio–eco interface is urgently needed. In general, nanomaterials interact with their surrounding environments, biotic and abiotic, immediately upon introduction into the environment. The behavior and fate of MONMs are influenced by the dynamics of the environment. Thus, understanding the interactions at the nano–bio–eco interface is necessary for selecting and designing MONMs with minimum adverse impacts. Despite the limitations of currently available techniques, careful characterization of nanomaterials and the choosing of methodologies that promote further risk assessment promise more reliable and accurate data output. Conventional toxicological analysis techniques lack the power to handle the large datasets generated from in vitro / in vivo observations. This paper provides a comprehensive review of the recent experimental and theoretical studies on the toxicity of MONMs mediated by two-way or three-way interactions. In the Perspectives, we also call for more open collaborations between industry, academia, and research labs to facilitate nanotoxicological studies focused specifically on interactions at the nano–bio–eco interface, leading to safe and effective nanotechnology for commercial, environmental, and medicinal use.